Effect of M-EMS current intensity on the subsurface segregation and internal solidification structure for bloom casting of 42CrMo steel. (9th August 2021) - Wang, Pu; Tie, Zhanpeng; Li, Shaoxiang; Lan, Peng; Tang, Haiyan; Zhang, Jiaquan
ABSTRACT: As-cast inherited defects are usually observed especially in quenched and tempered (QT) steels, such as 42CrMo due to macro-segregation. A three-dimensional numerical model has been presented to reveal the heat mass transportation and solidification behaviour of the molten steel in a 250 mm × 280 mm continuously cast bloom with and without M-EMS application. The reliability of the coupled model was proved by comparing the measured data of magnetic flux density with the calculated one along the centreline. The research indicates that the phenomena of a decrease in the solidification rate and an increase in molten steel washing velocity are observed as the current intensity increases from 0 to 450 A, which leads to a decrease of the minimum segregation degree by 0.039 and an increase of the width of the harmful negative segregation band by 3.6 mm. The washing effect that increases with the current intensity can reinforce the heat transfer between molten steel and solidification front and stimulate the formation of the equiaxed crystal. Accordingly, the average, local temperature gradient, and the superheat degree at the centre of mould exit decrease by 0.12, 2.62 K·mm −1, and 2.9 K, respectively, together with an increase of the equiaxed crystal ratio by about 9.44%. It suggests that the M-EMS may lead to the more serious subsurface negative segregation but can improve the equiaxed crystal ratio of bloom castings, which influences the heat treatment performance and flaw detection pass rate of subsequent rolled products.